How did the factory town turn into a culture producer? Ekaterinburg from UOLE to Biennale - Anna F. Filosyan (Управление культурой)
Ekaterinburg was founded in 1723 as a fortress and factory town to meet the needs of the central government in territorial expansion and to provide weapons and ammunition for new conquests. Over three hundred years of its existence, it has grown into a major cultural center of Russia, a hub of talented people and landmark projects. The history of cultural life in Ekaterinburg is traced through the constellation of cornerstone processes and establishment of core institutions. To give a deeper insight into the culture and its evolution, the article delves into the regional mentality factors that played a pivotal role in building the unique cultural landscape. They include such mentality features inherent in Ekaterinburg residents as love of freedom and rationality, ”marginality” at the junction of Europe and Asia and hope for “wild happiness.” The chronological analysis of the evolvement of cultural institutions, from the first theater to street art festivals and initiatives of outstanding personalities, focuses on such hallmarks of Ekaterinburg culture as the impact of culture enthusiasts (such as Onésime Claire, Ilya Makletsky), who quite often came as invited specialists, high popularity of cultural pastime among the population and its gradual democratization in the 19th century, mobilization of cultural development during the industrialization years and World War II, the concurrent existence of official and underground culture during the stagnation period, the legitimation of unofficial art and music associations during the post-Soviet years, the emergence of contemporary art and its interaction with the urban environment and, finally, the rethinking of the regional identity and industrial heritage through the prism of cultural projects of the last two decades. The article will be interesting to a broad readership for its extensive presentation of cultural processes in Ekaterinburg and for the author's perspective on the intrinsic essence of these processes. The article can be recommended as an entry point to the history of Ekaterinburg culture for students of creative specialties, analysts, and city culture managers.